More Success With the Optimal Motivational Pattern? A Prospective Longitudinal Study of Young Athletes in Individual Sports - Schmid, Michael J.; Charbonnet, Bryan; Conzelmann, Achim; Zuber, Claudia (Frontiers in Psychology, 2021)
It is widely recognized that achievement motivation is an important determinant for a successful sports career. Specific patterns of motivational constructs have recently demonstrated promising associations with future success in team sports like football and ice hockey (e.g., Zuber & Conzelmann, 2019b). The present study scrutinizes whether those patterns also exist in individual sports and whether they are able to predict future performance levels. A sample of 155 young individual athletes completed questionnaires assessing achievement goal orientations, achievement motives, and self-determination at t1. The person-oriented method LICUR was used to form clusters based on these motivational constructs in order to analyze the relations between these clusters and the performance level 2.5 years later (t2). Similar to the studies in team sports, four motivational patterns were observed at t1. The highly intrinsically achievement-oriented athletes were much more likely to compete internationally (OR = 2.12), compared to the failure-fearing athletes (OR = 0.29). Although team and individual sports differ in many respects, they nevertheless are characterized by similar and thus generalizable career-promoting motivational profiles: Regardless of the type of sport, the highly intrinsically achievement-oriented athletes consistently have the best potential for success.